Muon-spin relaxation study of the double perovskite insulators Sr2 BOsO6 (B = Fe, Y, In) - Williams, R. C.; Xiao, F.; Thomas, I. O.; Clark, S. J.; Lancaster, Tom; Cornish, G. A.; Blundell, S. J.; Hayes, W.; Paul, A. K.; Felser, Claudia; Jansen, M. (Journal of Physics: Condensed Matter, 2016)
We present the results of zero-field muon-spin relaxation measurements made on the double perovskite insulators Sr2 BOsO6 (B = Fe, Y, In). Spontaneous muon-spin precession indicative of quasistatic long range magnetic ordering is observed in Sr2FeOsO6 within the AF1 antiferromagnetic phase for temperatures below TN = 135 ± 2 K. Upon cooling below T2 ≈ 67 K the oscillations cease to be resolvable owing to the coexistence of the AF1 and AF2 phases, which leads to a broader range of internal magnetic fields. Using density functional calculations we identify a candidate muon stopping site within the unit cell, which dipole field simulations show to be consistent with the proposed magnetic structure. The possibility of incommensurate magnetic ordering is discussed for temperatures below TN = 53 K and 25 K for Sr2YOsO6 and Sr2InOsO6, respectively.
CRIS-Team Scopus Importer:2023-03-20
Keywords: density functional theory; double perovskite; incommensurate magnetic ordering; magnetic spin structures; muon-spin relaxation; transition metal oxide